Amateur runners’ motivations for participating in long-distance races by age, gender, and sports experience - Rosales Obando, Dannia Maria (2018)
Purpose: to examine the motives of amateur runners, to participate in an athletic race, considering their age group, sports experience and gender. Participants were 404 people (18 to 88 years of age, n = 271 men and n = 133 women, between 2 months and 40 years of sports experience, none professional). Results: the reasons for running relative to weight control tend to lose value as the sports experience increases (men r=-.121; p=.046; women r=-.187; p=.031), and the reasons for overcoming goals and competition tend to decrease its importance as it advances in age (men r=-.231; p<.001; women r=-.207; p=.017). This pattern was similar for both sexes. In addition, both for men and women, their main reasons for running were the reasons for recognition and the reasons related to meaning of life and self-esteem. Conclusion: despite the amateur nature of the subjects and their lack of professional sports preparation to compete in long-distance races, their motivational profile, regardless of sex, is characterized by the search for recognition, meaning of life and self-esteem through the practice of that activity. In addition, the health reasons explain little variance of the motivation for running in the sample, both in men and women.